Effects of vitamin D on kidney histology and trpv1 channels in doxorubicin-induced nephropathy - Gurel, Ali; Atli, Hasan; Kaya, Nalan; Onalan, Ebru; Kuloglu, Tuncay; Aygen, Bilge (E-Century Publishing Corp, 2015)
Doxorubicin (DXR) is an antineoplastic agent of the anthracycline group, and may show nephrotoxic effects in animal models and humans. We investigated changes in kidney tissue following doxorubicin treatment and the effects of vitamin D on kidney tissue and TRPV1 channels. In this study, 24 adult male Wistar Albino rats were used. The animals were divided into four groups of six animals. During the 14-day experiment period, Group I did not have any application. 200 IU/day cholecalciferol was administered orally to Group II. Group III received 10 mg/kg single dose of DXR intraperitoneally (IP); and Group IV had a single 10 mg/kg dose of IP DXR and 200 IU/day of oral cholecalciferol. At the end of the experiment, the rats were decapitated, and their kidney tissues were removed. TRPV1 expression and apoptosis were detected in the tissue section by using immunohistochemical, TUNEL and real timePCR (RT-PCR) techniques. The findings were examined and photographed with BH2 Olympus photomicroscope. As result of immunohistochemical staining, RT-PCR and examination with light microscope, it was found that the TRPV 1 immunoreactivity of the DXR group decreased in comparison with the control group, and the vitamin D application did not reverse this effect. Apoptosis detected by the TUNEL method tended to increase in the doxorubicin group and was relatively reversed with the administration of vitamin D. Tissue malondialdehyde (MDA) levels were observed to correlate with the findings of apoptosis. This study showed that vitamin D has anti-apoptotic and antioxidant effects on kidney tissue after DXR-induced injury.
Keywords: Doxorubicin; apoptosis; nephropathy; trpv1; vitamin D